La faune des sites mésolithiques et néolithique de la zone du Nil Bleu (Soudan Central) La fauna de los yacimientos mesolíticos y neolítico del área del Nilo Azul (Sudán Central) - Chaix, Louis (Complutum, 2003)
The results are presented of the analysis of the faunal remains collected during the excavations of the Mesolithic sites of Sheikh Mustafa and El Mahalab and the Early Neolithic site of Sheikh el Amin in the Blue Nile area south-east of Khartoum. Remains from the first two sites show a contrasting model, with intensive fishing and hunting at SM near the Blue Nile, similar to the scenario at the Saggai site on the main Nile, and a primary hunting orientation at AM in the Butana plain far from the river. The absence of molluscs at SM probably indicates the abandonment of the site before the end of the dry season. The big size of fish in the small sample of AM suggests that they were captured in the wadi deep waters, probably during the rainy season. At Sheikh el Amin the remains of fish and molluscs are fairly scarce, possibly indicating the lower weight of predatory economy. Bones from large and small livestock, however, are quite lower than in most other Neolithic sites of the area, insinuating a fundamentally hunting economy that benefited of the savanna humid conditions at the Early Neolithic period.